Overruled - Ferguson, Lana (Berkley Romance, 2025)
"Two divorce lawyers determined to share only beds but not hearts discover that love is something that can't be overruled in this steamy contemporary romance by Lana Ferguson, USA Today bestselling author of The Game Changer. Danica Pierce has one great love in her life: work. As one of the top divorce lawyers in Chicago, Danica lets her caseload keep her warm at night and has no problem being married to her job, not when love only ends in hurt. When the biggest case of her career gives her a shot at making partner, it seems like nothing could possibly stand in her way...except for her infuriating secret: she's sleeping with the enemy. Ezra Hart is known for charming his way in and out of a courtroom. In the matter of winning Danica Pierce's heart, however, he's been far less successful. With her verdict to keep things purely physical with no chance of appeal, Ezra struggles to show Danica he's more than the insufferable playboy she's pegged him to be-especially since they find themselves on opposing sides of Danica's most important case to date. While Dani and Ezra battle it out in the courtroom, the real trial is the one happening between them. When Dani realizes that everything she knows of Ezra might be hearsay-and that she's not the only one with emotional baggage-she must choose between her fear of trusting again and the feelings blossoming between her and the man she thought was her worst enemy"--